Changes in Human Amniotic Fluid Fibrinolytic Inhibitor Levels during Pregnancy - Aznar, J; Hernandez, A; Parrilla, J.J; Estelles, A; Gilabert, J (Thrombosis and Haemostasis, 1976)
The amniotic fluid (AF) when incubated with the patient’s own plasma diminishes the lytic activity of the plasma. It is suggested that this inhibition is due to the presence of fibrinolytic inhibitors in the AF. The inhibitors rate increases as pregnancy advances. Evaluating these inhibitors in a group of 65 women before and after the 38th week of pregnancy, a higher rate of fibrinolytic inhibitors is found after the 38th week. The said differences are statistically significant. For the moment it does not seem that the increasing of the inhibitors in the last part of pregnancy might be used as a fetal maturity test.